A Study on Calibre Spectra of Nerve Fibres Innervating Intercostal and Extraocular Muscles in Selected Muscles of a Few Mammalian Species - D J Prakash, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
A Study on Calibre Spectra of Nerve Fibres Innervating Intercostal and Extraocular Muscles in Selected Muscles of a Few Mammalian Species